PENGUKURAN KINERJA DENGAN METODE BALANCED SCORECARD DEPARTEMEN MAINTENANCE PT BICC BERCA CABLES - Lilik Setyawan (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Measuring company performance using Balanced Scorecard method (BSC) begins with SWOT analysis by elaborating internal factors and external factors of company. From the results of this analysis it is known conditions in the current maintenance department and what strategies should be applied. Employee performance is one of the benchmarks of success of a company so serious attention to the management of human resources is absolutely necessary. During this time, performance measurement conducted by PT. BICC BERCA Cables only assesses the employee's softskill and is subjective. Therefore, there should be a comprehensive or comprehensive measurement of HR performance as in Maintenance Department. The purpose of this research is to identify Key Performance Indicators (KPI) that can represent the achievement of human resource performance, to know and analyze the result of HR performance measurement, and to get improvement proposal to improve IKK that does not meet the expected target and identify IKK that can represent human resource performance. The results of HR performance identification resulted in 10 KPI consist of Hard Skill and Soft Skill. The results of the analysis found that several KPIs need to improve their performance, which is related to MTTR Energy cable from 3 hours to 2.7 hours (8.33%), Expense spare part from Rp 138,274,851 to Rp 125,000,000 (9.6%) per month, Repair electronic component, electrical and mechanical from Rp 30,000,000 to Rp 40,000,000 (25%), Training from 2 kalx meniadi 3 times a month (50%) and Improved Score Matrix from 70 to 75 (7.1%).